2018
DOI: 10.1002/celc.201801281
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable and Compressible Self‐Healing P(AA‐co‐AAm)/CoCl2 Hydrogel Electrolyte for Flexible Supercapacitors

Abstract: We report a novel tough self‐healing electrolyte on the basis of poly (acrylic acid‐co‐acrylamide) cross‐linked by divalent cobalt ions (Co2+) (P(AA‐co‐AAm)/CoCl2). Intermolecular and intramolecular hydrogen bonding work together with the metal‐coordination between Co2+ and carboxylic ions to form a hydrogel, which can resist various deformations. The hydrogel electrolyte exhibits excellent mechanical performance (elongation at break >1200 %, compressive stress >600 kPa and compressibility >90 %). The establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 56 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…It was clearly shown that the Li + ion conduction rate of DC‐GPE (41.2 mS cm −1 ) was more than 3 times higher than that of LiClO 4 solution electrolyte (12.3 mS cm −1 ) at room temperature. Meaningfully, this result is well beyond our previously reported HA‐GPE (31.1 mS cm −1 ) and other single cross‐linked P(AA‐AAM)/CoCl 2 networks hydrogel electrolyte (17.2 mS cm −1 ) reported by tang . The 3D network structure endows the hydrogel with outstanding mechanical properties and excellent water/ liquid electrolyte retention performance.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…It was clearly shown that the Li + ion conduction rate of DC‐GPE (41.2 mS cm −1 ) was more than 3 times higher than that of LiClO 4 solution electrolyte (12.3 mS cm −1 ) at room temperature. Meaningfully, this result is well beyond our previously reported HA‐GPE (31.1 mS cm −1 ) and other single cross‐linked P(AA‐AAM)/CoCl 2 networks hydrogel electrolyte (17.2 mS cm −1 ) reported by tang . The 3D network structure endows the hydrogel with outstanding mechanical properties and excellent water/ liquid electrolyte retention performance.…”
Section: Resultssupporting
confidence: 81%
“…Meaningfully, this result is well beyond our previously reported HA-GPE (31.1 mS cm À 1 ) and other single cross-linked P(AA-AAM)/CoCl 2 networks hydrogel electrolyte (17.2 mS cm À 1 ) reported by tang. [16,21] The 3D network structure endows the hydrogel with outstanding mechanical properties and excellent water/ liquid electrolyte retention performance. Besides, this porous structure may also provide a good channel for ion transport.…”
Section: Ionic Transport Mechanism Of Dc-gpementioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and co‐workers [ 171 ] fabricated a physically crosslinked, self‐healing poly (acrylic acid‐ co ‐stearyl methacrylate)/Fe 3+ hydrogel electrolyte for nanowire PANI flexible SCs. Tang and co‐workers [ 177 ] reported the stretchable and compressible self‐healing poly (acrylic acid‐ co ‐acrylamide)/CoCl 2 hydrogel electrolyte for flexible SC. In the case of electrostatic interactions between metal ions and carboxyl groups, the electrochemical stability of metal ions plays an important role in the selectivity of ESDs.…”
Section: Electrostatic Interactions Based Self‐healing Materials For mentioning
confidence: 99%